Clinical Outcomes and Experience of a Multiyear Consecutive Case Series of Total Knee Arthroplasty Procedures Conducted with a Bipolar Sealer System for Hemostasis - Sah, Alexander P. (The Journal of Knee Surgery, 2021)
Maximizing hemostasis during total knee replacement procedures remains a key challenge in current practice. Bipolar sealer technology achieves intraoperative hemostasis through tissue sealing and coagulation with adjustable radio frequency energy and a saline-irrigated tip. Optimal surgical site hemostasis is important to avoid potential complications such as hemarthrosis, wound drainage, increased pain, delayed discharge, and readmissions. The aim of this study is to evaluate the safety and effectiveness of the bipolar sealer device in primary knee replacement in the largest consecutive series to date. A consecutive, treatment-control series of subjects who underwent a primary total knee arthroplasty (TKA) utilizing a bipolar sealer for hemostasis, one subgroup with concomitant tranexamic acid (TXA) administration (n = 1599) and one subgroup without TXA administration (n = 3582), compared with a control group of primary TKA under tourniquet only (n = 667). Statistical analyses were performed through two-tailed unpaired t-tests. There was less total postoperative drain output and a lower overall transfusion rate in the bipolar sealer group (807ml ± 428) (2.5%) than the tourniquet only group (1290 ± 658, p = 0.001) (8.4%, p = 0.0001), respectively. Drainage output in bipolar sealer + TXA (450 ± 297 ml) was lower than the other two groups (bipolar sealer 807 ± 428 mL, p = 0.0001; tourniquet only 1290 ± 658 ml, p = 0.0001). The bipolar sealer group had a higher hematocrit at postoperative day 1 (POD1) (bipolar sealer: 33.1 ± 4.3 cc, tourniquet only: 32.5 ± 4.3 cc, p = 0.001) and at discharge (POD2, bipolar sealer: 31.5 ± 3.7 cc, tourniquet only: 30.2 ± 3.9 cc, p = 0.0001). There were zero reported serious adverse events related to hemostasis management in any group. The bipolar sealer system is a safe and effective instrument to achieve intraoperative hemostasis during primary TKA. The bipolar sealer group required significantly fewer postoperative blood product transfusions and maintained a higher hematocrit concentration at the time of discharge compared with subjects treated solely with tourniquet mediated hemostasis. Addition of TXA to local hemostasis methods may further reduce blood loss and transfusion requirements.Level of Evidence This is a Level III study.
Keywords: knee arthroplasty; hemostasis; blood transfusion; bipolar sealer; blood loss